The Effect of Financial and Non-Financial Factors on Firm Value - Kristi, Nuke Monika; Yanto, Heri (Accounting Analysis Journal, 2020)
This study aims to explain the impact of financial and non-financial factors, namely firm size, profitability, leverage, liquidity, activity ratio, CSR disclosures and environmental performance on firm value. This research is quantitative study with causality research design. Company Performance Rating Program in Environmental Management (PROPER) participating companies whose shares are listed on the IDX during 2015-2019 were the population of this study. The purposive sampling technique was chosen to obtain the sample of 35 companies with 140 units of analysis. This research applied a multiple linear regression test on panel data collected from secondary data. The results show the firm value can be explained by firm size, profitability, and activity ratio in a positive direction. Meanwhile, the negative influence is shown by leverage and liquidity and CSR disclosure & environmental performance cannot influence the firm value significantly. Managers are expected can optimize their asset management, because firm size, profitability, and activity ratio have a positive and significant effect on firm value and be careful of using debt, because liquidity and leverage are proven to have negative effect on firm value.